The Role of the Majlis Salawat wa Ta'lim in Enhancing Community Cohesion and Islamic Understanding at Raudlatul Ulum Islamic Boarding School - Romdloni, Ahmad Faidly; Barizi, Ahmad (Yayasan Centre for Studying and Milieu Development of Indonesia (CESMiD), 2024)
This study explores the role of the Salawat wa ta'lim majlis at Raudlatul Ulum Islamic Boarding School in enhancing social cohesion among the surrounding community through increased Islamic understanding and love for the salawat. The majlis serves as a platform to strengthen the relationships between students, alums, and the community through routine activities involving the recitation of Surah Yaasiin, tahlil, salawat, and brief sermons. Using a qualitative approach, this study examines the majlis's role in instilling Islamic values and strengthening the spiritual bonds within the community. Data was collected through observation, interviews, and documentation, with key informants including leaders of the boarding school and majlis participants. The findings indicate that the majlis activities enhance the participants' religious understanding and strengthen social ties, motivating them to draw closer to Allah. Additionally, the recitation of salawat, particularly salawat Qiyam and Maulid Ad-Diba', positively impacts the spiritual well-being of the participants and fosters a more profound love for Prophet Muhammad.